Everyday administrative burdens and inequality - Lucie Martin; Liam Delaney; Orla Doyle (University College Dublin, UCD School of Economics, 2022)
Administrative burdens may deepen inequality by creating costly experiences for vulnerable groups. Research to date typically focuses on how burdens affect decisions in specific policy contexts, thus little is known about everyday experiences of burdens and their distribution in society. This is the first study to document everyday administrative experiences, accounting for time and emotional costs across ten domains: tax, retirement, government benefits, bills, goods and services, savings, debt, health, childcare, and adult care. Results from 2,243 UK adults show that administrative tasks are a significant part of life (one hour per day). Time and emotional costs vary by domain; government benefits emerge as particularly costly. There is evidence that administrative burdens are regressive, not only through their effects on decisions, but through their unequal distribution in society. Those in poor health and financial insecurity focus on tasks salient to them (e.g. benefits, health, debt), but are less likely to engage in beneficial longer-term tasks (e.g. savings, retirement), and suffer higher emotional costs from engaging in tasks relevant to their disadvantage, compared to non-disadvantaged groups. A choice experiment shows that (hypothetical) burdens discourage beneficial action in general, but even more so for some disadvantaged groups.
Keywords: D91; I30; J10; 330; administrative burden; inequality; time-use; subjective well-being; experiment; Bürokratie; Zeitverwendung; Befolgungskosten; Emotion; Stress; Soziale Gruppe; USA